Removal versus retention of asymptomatic third molars in mandibular angle fractures: a randomized controlled trial. Issue 5 (May 2016) - McNamara, Z.; Findlay, G.; O'Rourke, P.; Batstone, M.
Abstract: The treatment dilemma provided by asymptomatic third molars in mandibular angle fractures remains controversial. This prospective randomized controlled trial was undertaken to determine whether there is an advantage to extraction or retention of the third molar whilst repairing a mandibular angle fracture. Sixty-four patients were allocated randomly to the two treatment groups. All underwent open reduction and internal fixation (ORIF) with standard postoperative care. The primary outcome measure was uncomplicated fracture healing. Secondary measures were surgical duration, malocclusion, wound healing, nerve injury, and return to theatre. All patients had uncomplicated fracture healing. The incidence of nerve injury was 16% for the retention group compared with 39% for the removal group ( P = 0.038). The average operating time for ORIF and third molar retention cases was 58.5 min and for ORIF and third molar removal cases was 66.3 min ( P = 0.26). There was no statistically significant difference between groups for wound healing, occlusion outcomes, or return to theatre. Given the additional risk of nerve injury and the additional operating time required for removal of a third molar, in the absence of an absolute indicator for removal of the third molar, it appears justifiable to advise retaining the tooth in the line of a mandibular angle fracture.